A Mixed Complementarity-Based Equilibrium Model of Natural Gas Markets - Gabriel, Steven A.; Kiet, Supat; Zhuang, Jifang (Operations Research, 2005)
We present a new multiseasonal, multiyear, natural gas market equilibrium model based on the concept of a competitive equilibrium involving the market participants: producers, storage reservoir operators, peak gas operators, pipeline operators, marketers, and consumers. The first three classes are depicted as price-takers consistent with perfect competition. The pipeline operations are described with regulated tariffs, but also involve “congestion pricing” as a mechanism to allocate scarce pipeline capacity. The marketers are price-takers in all markets except in sales to consumers, in which they compete as Nash-Cournot players. Finally, consumers are described by demand curves for each of the four sectors: residential, commercial, industrial, and electric power. We show that the equilibrium model is an instance of a mixed nonlinear complementarity problem (NCP) and provide sufficient detail not generally seen in previous complementarity models of natural gas. The NCP formulation is derived from considering the Karush-Kuhn-Tucker optimality conditions of the optimization problems faced by these participants. Under mild conditions, we show that this NCP has a solution, and under additional reasonable conditions, we show that the market prices are unique. We also validate the model on a representative sample network with nine market participants and three seasons, using four scenarios.